Вимоїни на піщано-рідкоскляних формах та стрижнях, що структуровані в паро-мікрохвильовому середовищі - Солоненко, Людмила (Physico-technological Institute of Metals and Alloys, 2023)
The purpose of the research was to elucidate the leakage defect occurrence mechanism and ways to prevent its occurrence on foundry molds and cores made by steam-microwave solidification from quartz sand cladded with sodium silicate solute. The studies used quartz sand grade 1K1O102, clad with liquid sodium glass, water of technical purity, gypsum grade G-22 and its mixtures with certain technological additives – Fe2O3·TiO2, CoO·Al2O3·2SiO2, CoO, Cr2O3, SiC, B4C. For cores manufacturing polypropylene core boxes have been used. Specimens of nested elements in core boxes have been made from pure gypsum, as well as from gypsum mixture with 1 % (by mass) of technological additive. For mixtures in steammicrowave environment structuring, water charge has been used – polyurethane sponge previously impregnated with 1 g of water. Vibration-compacted mixtures structuring has been performed by microwave radiation at magnetron power of 700 W and radiation frequency of 2,45 GHz for 7–8 minutes. Leakage defects on cores surfaces have been observed and evaluated visually. Gypsum samples Ø 40×70 mm (gypsum samples have been structured with water and dried at 200 ± 5 °С for 3 hours) heating rate by microwave radiation has been calculated from their temperature changing measurement in 2–3 minutes of their heating. Samples temperature has been measured with chromel-alumel thermocouple completed with electronic potentiometer. Heating time has been recorded with stopwatch with an accuracy of 1 s. Mechanism description has been elaborated and causes of leakage defects on foundry molds and cores from sand-sodiumsilicate mixtures (quartz sand clad with sodium silicate solute) structured by steam-microwave solidification method appearance have been established. Leakage defects occurrence on foundry molds and cores technological ways of prevention, water-structured gypsum and its mixtures with technological additives of 1 % temperature rising rate have been established. For the first time leakage defects formation mechanism has been investigated and its description has been developed. Their occurrence prevention conditions on foundry molds and cores from quartz sand cladded with sodium silicate solute structured by steam-microwave solidification method have been defined. Obtained data will be useful for molds and cores rigging manufacturing, which have been structured by steam-microwave solidification method with water-soluble binder.